Antibiotic prescribing for childhood febrile illness by primary care doctors in Malaysia - Teng, C.L.; Nik-Sherina, H.; Ng, Chirk Jenn; Chia, Y.C.; Atiya, A.S. (Wiley, 2006)
Aim: Fever in children, a mostly benign and self-limiting illness, is often viewed with consternation by the care givers. It results in early consultation and excessive use of antipyretics and antibiotics. In this study, we document the prescribing practice of doctors from three primary care settings in Malaysia and identify the predictors of antibiotic prescription. Methods: Interview of care givers bringing febrile children (age <= 12 years) to three primary care settings: public primary care clinics, private general practice clinics and a university-based primary care clinic. Results: Data from 649 children were analysed. Mean age of children 4.1 years and 55 were boys. One-third of the children had prior consultation for the same episode of fever. About 80 of the febrile children were diagnosed to have upper respiratory tract infection, viral fever and gastroenteritis. Overall antibiotic prescribing rate was 36.6 (public primary care clinic 26.8, private general practice clinic 70.0 and university-based primary care clinic 32.2). Independent predictors of antibiotic prescription were: clinic setting, longer duration of fever (> 7 days), higher temperature (> 38 degrees C) and the diagnosis of upper respiratory tract infections. After controlling for demographic and clinical factors, antibiotic prescription in private general practice clinic was seven times higher than public primary care clinic (odds ratio 7.1, 95 confidence interval 4.0-12.7), and 1.6 times higher than university-based primary care clinic (odds ratio 1.6, 95 confidence interval 1.0-2.5). Conclusion: Differences in the patients' demographic and clinical characteristics could not adequately explain the high antibiotic prescribing rate in private general practice clinics. This inappropriately high antibiotic prescribing for febrile children in private general practice clinics is a suitable target for future intervention.